Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.4 - Multiplying Polynomials - 4.4 Exercises: 34

Answer

$p^{2}-2p-24$

Work Step by Step

We are given the expression $(p+4)(p-6)$. We can find the product of this expression using the FOIL method. First terms: $p\times p=p^{2}$ Outer terms: $p\times-6=-6p$ Inner terms: $4\times p=4p$ Last terms: $4\times-6=-24$ Adding together: $p^{2}+(-6p)+4p+(-24)=p^{2}-6p+4p-24=p^{2}-2p-24$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.